Zif-based derived porous carbon-molecular sieve composite material, and preparation method and application thereof
Patent Information
- Application Number
- CN202610742851.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-05-27
- Publication Date
- 2026-08-28
AI Technical Summary
[0006]本发明的目的是为了克服现有技术存在的针对含氧化合物脱除吸附剂材料的单一性及吸附性能不足的问题,提供了一种ZIF基衍生多孔碳-分子筛复合材料及其制备方法和应用
[0040] According to the preparation method of ZIF-based derived porous carbon-molecular sieve composite material of the present invention, the composite material formed by coordination reaction of organic ligands with transition metal salts on the outside of the molecular sieve and carbonization has the advantages of large specific surface area, high porosity, three-dimensional carbon framework and controllable morphology. After pyrolysis, it forms amorphous carbon with high surface defects and high specific surface area, mainly composed of pyridine nitrogen. Due to the introduction of nitrogen atoms, some oxygen groups combined with carbon atoms are replaced to form CN bonds. Pyridine nitrogen can generate positive charges on its adjacent carbon atoms, which is conducive to forming acid-base pairs with oxygen-containing functional groups (-COOH, -OH) and improving adsorption selectivity. While cleaning the residual metal in the carbonized material with acid solution, the acid can dissolve amorphous silica-alumina impurities or amorphous phases blocking the pores in the molecular sieve, improve the uniformity of specific surface area and pore size distribution, and at the same time, some sodium ions are replaced by hydrogen ions, enhancing the adsorption selectivity for polar molecules. The ZIF-based derived porous carbon-molecular sieve composite material prepared according to the method of the present invention has a strong adsorption capacity for oxygen-containing compounds.
Smart Images

Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention relates to the field of coal chemical adsorbent technology, specifically to a ZIF-based derived porous carbon-molecular sieve composite material, its preparation method, and its application. Background Technology
[0002] Coal produced by Fischer-Tropsch synthesis contains a wide variety of oxygen-containing compounds in different fractions of hydrocarbon products, and efficient removal is a key step in the upgrading process. The core of adsorption deoxygenation technology lies in the selection of adsorbents. An ideal adsorbent needs to have: (1) an ordered pore structure to achieve molecular sieving effect; (2) a high specific surface area to provide sufficient adsorption sites; (3) a large adsorption capacity; and (4) a low heat of adsorption. FUA-type molecular sieves are a type of material with a regular microporous crystal structure. Their topology is derived from natural octahedral zeolite and has a highly open and interconnected three-dimensional pore system. The structure consists of large-aperture windows composed of twelve-membered rings that are interconnected to form a uniform supercage cavity, giving the molecular sieve an extremely high specific surface area and excellent adsorption capacity. It can efficiently accommodate and separate molecules with large molecular sizes, and is therefore widely used in adsorption separation, catalysis, wastewater treatment and energy storage. FUA-type molecular sieves mainly include two types, X-type and Y-type, which have different silicon-to-aluminum ratios. Both are widely used in the preparation of adsorption materials due to their structural advantages. However, in practical applications, single molecular sieve materials still face problems such as insufficient adsorption selectivity and limited adsorption performance, which restricts their industrial application effectiveness. Therefore, functional modification to adjust the surface properties and pore environment of molecular sieves is of great significance for developing high-performance oxygen-containing compound adsorbents.
[0003] The hydrocarbon products produced by indirect liquefaction of coal through Fischer-Tropsch synthesis have vastly different molecular weights and structures with varying carbon number distributions. Furthermore, the types of oxygen-containing compounds in hydrocarbon products with different carbon number distributions are complex. Among existing deoxygenation technologies, adsorption methods are widely used in removal processes due to their advantages such as low temperature, low pressure, and ease of operation. Currently, the adsorbent technology for removing oxygen-containing compounds from hydrocarbons mainly focuses on the combination and modification of molecular sieve adsorbents and alumina adsorbents.
[0004] Patent application CN116023982A discloses an adsorbent for adsorbing oxygen-containing compounds and a method for adsorbing oxygen-containing compounds. The adsorbent includes a first adsorbent (at least one of modified activated carbon, 13X molecular sieve, and 5A molecular sieve), suitable for adsorbing esters and / or ketones; and a second adsorbent (at least one of alumina, silica gel, 13X molecular sieve, and 5A molecular sieve), suitable for adsorbing alcohols and / or acids. The amount of adsorbent used needs to be adjusted or the adsorbents used in combination need to be adjusted according to the type of oxygen-containing compound. Patent application CN115722189B discloses an adsorbent for removing oxygen-containing compounds from low-molecular-weight hydrocarbons. This adsorbent contains Y-type molecular sieves, alumina and / or silica, and modifying components. The modifying components contain one or more of sodium salts, potassium salts, magnesium salts, calcium salts, zirconium salts, molybdenum salts, and zinc salts, as well as carbon nanotubes. This adsorbent improves the adsorption of weakly polar macromolecular oxygen-containing compounds, but it is only effective for removing oxygen-containing compounds from C2-C5 low-molecular-weight hydrocarbons.
[0005] The hydrocarbon products from different fractions of coal produced through the Fischer-Tropsch indirect liquefaction process generally contain a complex variety of oxygen-containing compounds (such as alcohols, aldehydes, and ketones). These oxygen-containing compounds exhibit significant differences in polarity, molecular size, and boiling point, leading to limitations in the selective adsorption and separation performance of traditional single-material adsorbents. Specifically, a single adsorbent cannot simultaneously meet the adsorption requirements of different oxygen-containing compounds and is limited in its removal of high-carbon-number oxygen-containing compounds. These shortcomings restrict the application of adsorbents in industrial applications such as hydrocarbon refining and the separation of high-value chemicals. Summary of the Invention
[0006] The purpose of this invention is to overcome the problems of limited adsorption capacity and singularity of existing adsorbent materials for the removal of oxygen-containing compounds, and to provide a ZIF-based derived porous carbon-molecular sieve composite material, its preparation method, and its applications. The ZIF-based derived porous carbon-molecular sieve composite material prepared according to the method of this invention exhibits a strong adsorption capacity for oxygen-containing compounds.
[0007] To achieve the above objectives, the present invention provides a method for preparing ZIF-based derived porous carbon-molecular sieve composite materials, the method comprising the following steps: (1) The fly ash and the first alkaline compound are mixed once, and the resulting mixture is calcined to obtain fly ash clinker. The fly ash clinker and the acid solution are mixed a second time and a solid-liquid separation is performed once to separate the first solid product and the first liquid product. (2) The first solid product, the second alkaline compound and water are mixed twice and then separated into solid and liquid phases twice. The separated second liquid product and the first liquid product are mixed three times. The resulting mixture, the sodium-containing salt solution and the amorphous directing agent are then subjected to a crystallization reaction to obtain a molecular sieve. (3) The molecular sieve, transition metal salt solution and organic ligand solution are mixed, and the resulting mixture is aged. The aged product is then separated into solid and liquid phases, and the separated solid product is calcined, acid washed and dried under an inert atmosphere.
[0008] Preferably, in step (1), the mass ratio of the fly ash to the first alkaline compound is 1:0.5-3.
[0009] Preferably, the first alkaline compound is sodium hydroxide and / or sodium carbonate.
[0010] Preferably, in step (1), the calcination conditions include: a temperature of 450-900℃ and a time of 0.5-4h.
[0011] Preferably, in step (1), the mass ratio of the fly ash clinker to the acid solution is 1:1-60.
[0012] Preferably, the acid solution is at least one selected from hydrochloric acid solution, sulfuric acid solution, nitric acid solution and acetic acid solution.
[0013] Preferably, the concentration of the acid solution is 10-50% by weight.
[0014] Preferably, in step (2), the mass ratio of the first solid product, the second alkaline compound, and the water is 1:(0.5-70):(0.5-500).
[0015] Preferably, the second alkaline compound is at least one selected from sodium hydroxide, sodium carbonate, potassium hydroxide, and sodium bicarbonate.
[0016] Preferably, in step (2), the amounts of the second liquid phase product and the first liquid phase product are such that the molar ratio of SiO2 / Al2O3 in the resulting mixture is 1-8.
[0017] Preferably, in step (2), the amounts of the obtained mixture and the sodium-containing salt solution are such that the Na2O / SiO2 molar ratio in the obtained mixture and the sodium-containing salt solution is 2-3.
[0018] Preferably, the sodium-containing salt solution is at least one of sodium chloride solution, sodium nitrate solution, sodium bromide solution, and sodium aluminate solution.
[0019] Preferably, the concentration of the sodium-containing salt solution is 5-15% by weight.
[0020] Preferably, in step (2), the mass ratio of the obtained mixture to the amorphous directing agent is 1:0.01-1.5.
[0021] Preferably, in step (2), the conditions for the crystallization reaction include: a temperature of 60-108°C and a time of 1-48h.
[0022] Preferably, the method further includes preparing the amorphous directing agent by reacting a silicon source, an aluminum source, an alkaline compound, and water at 40-100°C for 0.5-8 hours.
[0023] Preferably, the silicon source is at least one of sodium silicate, silica sol, silicic acid, and water glass.
[0024] Preferably, the aluminum source is at least one selected from aluminum sulfate, boehmite, aluminum sol, and sodium aluminate.
[0025] Preferably, the alkaline compound is at least one selected from sodium hydroxide, potassium hydroxide, sodium bicarbonate, and sodium carbonate; Preferably, the amounts of the silicon source, the aluminum source, the alkaline compound, and the water are such that the molar ratio of Na2O / Al2O3 / SiO2 / H2O in the product is (1-10):1:(1-30):(1-500).
[0026] Preferably, in step (3), the mass ratio of the molecular sieve, the transition metal salt solution and the organic ligand solution is 1:(1-5):(1-5).
[0027] Preferably, the transition metal salt solution is at least one selected from zinc nitrate solution, zinc chloride solution, cobalt nitrate solution, cobalt chloride solution, ferric nitrate solution, ferric chloride solution, copper nitrate solution, copper chloride solution, and nickel nitrate solution.
[0028] Preferably, the organic ligand solution is at least one selected from 2-methylimidazole, imidazole-2-carboxaldehyde, benzimidazole, and terephthalic acid.
[0029] Preferably, in step (3), the solvent used for the transition metal salt solution is at least one of methanol, ethanol, isopropanol, water, and n-butanol.
[0030] Preferably, the concentration of the transition metal salt solution is 0.5-5% by weight.
[0031] Preferably, in step (3), the solvent used for the organic ligand solution is at least one of methanol, ethanol, isopropanol, water, and n-butanol.
[0032] Preferably, the concentration of the organic ligand solution is 0.5-5% by weight.
[0033] Preferably, in step (3), the aging conditions include: a temperature of 10-40°C and a time of 8-48h.
[0034] Preferably, in step (3), the calcination conditions include: a temperature of 550-1000℃ and a time of 1-4h.
[0035] Preferably, the acid solution used in the pickling process is at least one of hydrochloric acid solution, nitric acid solution, acetic acid solution and sulfuric acid solution.
[0036] Preferably, the concentration of the acid solution used in the pickling process is 0.5-2M.
[0037] A second aspect of the present invention provides a ZIF-based derived porous carbon-molecular sieve composite material prepared by the method described above.
[0038] The third aspect of this invention provides the application of the ZIF-based derived porous carbon-molecular sieve composite material described above in the adsorption process of oxygen-containing compounds.
[0039] Preferably, the oxygen-containing compound is a C5-C9 organic alcohol and / or a C5-C7 organic acid.
[0040] According to the preparation method of ZIF-based derived porous carbon-molecular sieve composite material of the present invention, the composite material formed by coordination reaction of organic ligands with transition metal salts on the outside of the molecular sieve and carbonization has the advantages of large specific surface area, high porosity, three-dimensional carbon framework and controllable morphology. After pyrolysis, it forms amorphous carbon with high surface defects and high specific surface area, mainly composed of pyridine nitrogen. Due to the introduction of nitrogen atoms, some oxygen groups combined with carbon atoms are replaced to form CN bonds. Pyridine nitrogen can generate positive charges on its adjacent carbon atoms, which is conducive to forming acid-base pairs with oxygen-containing functional groups (-COOH, -OH) and improving adsorption selectivity. While cleaning the residual metal in the carbonized material with acid solution, the acid can dissolve amorphous silica-alumina impurities or amorphous phases blocking the pores in the molecular sieve, improve the uniformity of specific surface area and pore size distribution, and at the same time, some sodium ions are replaced by hydrogen ions, enhancing the adsorption selectivity for polar molecules. The ZIF-based derived porous carbon-molecular sieve composite material prepared according to the method of the present invention has a strong adsorption capacity for oxygen-containing compounds. Detailed Implementation
[0041] The following provides a detailed description of specific embodiments of the present invention. It should be understood that the specific embodiments described herein are for illustrative and explanatory purposes only and are not intended to limit the scope of the invention.
[0042] The endpoints and any values of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of the various ranges, the endpoint values of the various ranges and individual point values, and individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.
[0043] The preparation method of the ZIF-based derived porous carbon-molecular sieve composite material of the present invention includes the following steps: (1) The fly ash and the first alkaline compound are mixed once, and the resulting mixture is calcined to obtain fly ash clinker. The fly ash clinker and the acid solution are mixed a second time and a solid-liquid separation is performed once to separate the first solid product and the first liquid product. (2) The first solid product, the second alkaline compound and water are mixed twice and then separated into solid and liquid phases twice. The separated second liquid product and the first liquid product are mixed three times. The resulting mixture, the sodium-containing salt solution and the amorphous directing agent are then subjected to a crystallization reaction to obtain a molecular sieve. (3) The molecular sieve, transition metal salt solution and organic ligand solution are mixed, and the resulting mixture is aged. The aged product is then separated into solid and liquid phases, and the separated solid product is calcined, acid washed and dried under an inert atmosphere.
[0044] In step (1), the mass ratio of fly ash to the first alkaline compound can be 1:0.5-3, preferably 1:0.8-2.5, and more preferably 1:1-2. The first alkaline compound can be sodium hydroxide and / or sodium carbonate. In the most preferred embodiment, the first alkaline compound is sodium hydroxide.
[0045] In step (1), the primary mixing process can be carried out under grinding conditions. The grinding process can be carried out in a ball mill. The grinding conditions may include: a rotation speed of 50-70 r / min and a time of 5-15 min.
[0046] In step (1), the calcination conditions may include a temperature of 450-900℃ and a time of 0.5-4h. Preferably, the calcination conditions include a temperature of 500-800℃ and a time of 1-3h. The calcination process can be carried out in a muffle furnace.
[0047] In step (1), the mass ratio of the fly ash clinker to the acid solution can be 1:1-60, preferably 1:5-50. The acid solution can be at least one of hydrochloric acid solution, sulfuric acid solution, nitric acid solution, and acetic acid solution. In the most preferred embodiment, the acid solution is hydrochloric acid solution. The concentration of the acid solution can be 10-50% by weight, preferably 15-40% by weight.
[0048] In step (1), preferably, the solid-liquid separation is performed by filtration.
[0049] In step (2), the mass ratio of the first solid product, the second alkaline compound, and the water can be 1:(0.5-70):(0.5-500), preferably 1:(1-60):(1-300), and more preferably 1:(5-50):(5-200). The second alkaline compound can be at least one of sodium hydroxide, sodium carbonate, potassium hydroxide, and sodium bicarbonate. In the most preferred embodiment, the second alkaline compound is sodium hydroxide.
[0050] In step (2), the amounts of the second liquid phase product and the first liquid phase product are such that the molar ratio of SiO2 / Al2O3 in the resulting mixture can be 1-8, preferably 2-6.
[0051] In step (2), the amounts of the obtained mixture and the sodium-containing salt solution are such that the Na₂O / SiO₂ molar ratio in the obtained mixture and the sodium-containing salt solution is 2-3, preferably 2.2-2.8. The sodium-containing salt solution can be at least one of sodium chloride solution, sodium nitrate solution, sodium bromide solution, and sodium aluminate solution. In the most preferred embodiment, the sodium-containing salt solution is a sodium aluminate solution. The concentration of the sodium-containing salt solution can be 5-15% by weight, preferably 8-12% by weight.
[0052] In step (2), the mass ratio of the obtained mixture to the amorphous directing agent can be 1:0.01-1.5, preferably 1:0.05-1.2.
[0053] In step (2), the three mixing processes can be carried out under stirring. The conditions for the three mixing processes may include: a stirring rate of 100-300 r / min and a time of 0.5-5 h.
[0054] In step (2), the conditions for the crystallization reaction may include: a temperature of 60-108°C and a time of 1-48 h. Preferably, the conditions for the crystallization reaction include: a temperature of 80-105°C and a time of 12-24 h. The crystallization reaction can be carried out in a hydrothermal reactor. The crystallization reaction process may further include: repeatedly filtering and washing the product obtained from the crystallization reaction until the pH of the washing solution is 6.5-7.5, and then drying it. The drying conditions may include: a temperature of 60-120°C and a time of 8-24 h. The drying process can be carried out in various conventional drying ovens in the art.
[0055] In step (2), preferably, the secondary solid-liquid separation is performed by filtration.
[0056] In the method described in this invention, the method further includes preparing the amorphous directing agent by reacting a silicon source, an aluminum source, an alkaline compound, and water at 40-100°C for 0.5-8 hours. The silicon source may be at least one of sodium silicate, silica sol, silicic acid, and water glass. In the most preferred embodiment, the silicon source is sodium silicate. The aluminum source may be at least one of aluminum sulfate, boehmite, aluminum sol, and sodium aluminate. In the most preferred embodiment, the aluminum source is boehmite. The alkaline compound is at least one of sodium hydroxide, potassium hydroxide, sodium bicarbonate, and sodium carbonate. In the most preferred embodiment, the alkaline compound is sodium hydroxide. The amounts of the silicon source, the aluminum source, the alkaline compound, and the water are such that the molar ratio of Na₂O / Al₂O₃ / SiO₂ / H₂O in the product is (1-10):1:(1-30):(1-500), preferably (1-8):1:(5-25):(5-300).
[0057] In step (3), the mass ratio of the molecular sieve, the transition metal salt solution, and the organic ligand solution can be 1:(1-5):(1-5), preferably 1:(1.5-4):(1.5-4). The transition metal salt solution can be at least one of zinc nitrate solution, zinc chloride solution, cobalt nitrate solution, cobalt chloride solution, ferric nitrate solution, ferric chloride solution, copper nitrate solution, copper chloride solution, and nickel nitrate solution. In the most preferred embodiment, the transition metal salt solution is zinc nitrate solution. The organic ligand solution can be at least one of 2-methylimidazole, imidazole-2-carboxaldehyde, benzimidazole, and terephthalic acid. In the most preferred embodiment, the organic ligand solution is 2-methylimidazole.
[0058] In step (3), the solvent used for the transition metal salt solution can be at least one selected from methanol, ethanol, isopropanol, water, and n-butanol. In the most preferred embodiment, the transition metal salt solution is methanol. The concentration of the transition metal salt solution can be 0.5-5% by weight, preferably 1-4.5% by weight.
[0059] In step (3), the solvent used for the organic ligand solution can be at least one selected from methanol, ethanol, isopropanol, water, and n-butanol. In the most preferred embodiment, the solvent used for the organic ligand solution is methanol. The concentration of the organic ligand solution can be 0.5-5% by weight, preferably 1-4.5% by weight.
[0060] In step (3), the aging conditions may include a temperature of 10-40°C and a time of 8-48 hours. Preferably, the aging conditions include a temperature of 15-30°C and a time of 12-24 hours. The aging process can be carried out in various conventional reaction apparatuses in the art.
[0061] In step (3), the calcination conditions may include a temperature of 550-1000°C and a time of 1-4 hours. Preferably, the calcination conditions include a temperature of 600-900°C and a time of 2-3 hours. The calcination process can be carried out in a tube furnace. The inert atmosphere may be provided by at least one of nitrogen, helium, and argon. In the most preferred embodiment, the inert atmosphere is provided by argon.
[0062] In step (3), the acid solution used in the pickling process can be at least one of hydrochloric acid solution, nitric acid solution, acetic acid solution, and sulfuric acid solution. In the most preferred embodiment, the acid solution used in the pickling process is hydrochloric acid solution. The concentration of the acid solution used in the pickling process can be 0.5-2M, preferably 0.5-1.5M.
[0063] In step (3), preferably, the solid-liquid separation is performed by centrifugation. The conditions for centrifugation may include: a rotation speed of 5000-8500 r / min and a time of 3-15 min. Preferably, the washing reagent used in the centrifugation process is methanol.
[0064] In step (3), the drying conditions may include a temperature of 40-60°C and a time of 8-24 hours. Preferably, the drying conditions include a temperature of 45-55°C and a time of 10-15 hours. The drying process can be carried out in a vacuum drying oven.
[0065] The present invention also provides a ZIF-based derived porous carbon-molecular sieve composite material prepared by the above method. This ZIF-based derived porous carbon-molecular sieve composite material has a large specific surface area and high porosity, enabling selective adsorption of oxygen-containing compounds.
[0066] This invention also provides the application of the ZIF-based derived porous carbon-molecular sieve composite material in the adsorption process of oxygen-containing compounds. The oxygen-containing compounds can be C5-C9 organic alcohols and / or C5-C7 organic acids. In practical applications, the ZIF-based derived porous carbon-molecular sieve composite material exhibits an adsorption capacity of up to 138.90 mg / g for C7-C9 alcohols.
[0067] The following examples further illustrate the ZIF-based derived porous carbon-molecular sieve composite material, its preparation method, and its application according to the present invention. The examples are implemented based on the technical solution of the present invention, providing detailed implementation methods and specific operating procedures; however, the scope of protection of the present invention is not limited to the following examples.
[0068] Unless otherwise specified, the experimental methods used in the following embodiments are conventional methods in the art. Unless otherwise specified, the experimental materials used in the following embodiments are commercially available.
[0069] In the following examples and comparative examples, the relevant parameters of the prepared samples were tested according to the following methods: Pore volume and specific surface area testing: BET tests were performed on a BELSORP-max fully automated specific surface area and porosity analyzer. The desorption area of the sample after nitrogen adsorption at liquid nitrogen temperature was determined and recorded using the chemical pulse adsorption method. The sample was pretreated at 350℃ for 8 hours before the test. The total specific surface area was calculated using the BET formula, and the pore size distribution was calculated using the NLDFT model.
[0070] Adsorption performance test: After the prepared sample was mixed with porous alumina and granulated, 20g was loaded into the adsorption column. Under the condition of agent-to-oil ratio of 0.6, C8-C10 olefin raw material with an oxygen compound concentration of about 10,000 ppm was fed to the top of the adsorption column by a peristaltic pump. The main components and contents are as follows: C8 olefin 5 wt%, C9 olefin 30.5 wt%, C10 olefin 21.2 wt%, and alkanes 35.5 wt%. After the test, the removal rate of acid and alcohol oxygen compounds after adsorption treatment of the feed liquid was calculated, including at least one of valeric acid, hexanoic acid, hexanol, heptanol, octanol and nonanol. The formula is shown in formula (1), where C0 is the concentration of the target oxygen compound in the imported logistics and C1 is the concentration of the target oxygen compound in the exported logistics.
[0071] Equation (1) Example 1 Preparation of amorphous directing agents: An aluminum source solution was prepared by mixing 10g of boehmite, 11g of sodium hydroxide, and 140g of deionized water. Then, a silicon source solution was prepared by dissolving 95g of sodium silicate in 160g of deionized water and stirring for 1 hour. The aluminum and silicon source solutions were mixed and reacted at 80°C for 5 hours to obtain amorphous directing agent A1. The molar ratio of Na2O / Al2O3 / SiO2 / H2O in the obtained amorphous directing agent A1 was 7:1:5:300.
[0072] Preparation of ZIF-derived porous carbon-molecular sieve composites: (1) Grind and mix 50g of fly ash (the composition is shown in Table 1, the same below) with 60g of sodium hydroxide, and then place the resulting mixture in a muffle furnace and calcine it at 530℃ for 2h. After cooling, fly ash clinker is obtained. Mix fly ash clinker and hydrochloric acid solution with a concentration of 33.3% by weight at a mass ratio of 1:15 and filter. Collect the filtrate to obtain aluminum-rich liquid and separate the residue after filtration.
[0073] (2) Take 20g of the residue filtered in step (1), 100g of sodium hydroxide and 300g of deionized water, stir and mix evenly, and filter the filtrate to obtain the silicon-rich liquid. Mix the aluminum-rich liquid and the silicon-rich liquid, and adjust the dosage ratio so that the SiO2 / Al2O3 ratio in the resulting mixture is 3.5. Then add a sodium aluminate solution with a concentration of 10% by weight, and adjust the dosage so that the Na2O / SiO2 molar ratio in the resulting mixture is 2.7. Add amorphous directing agent A1, and the mass ratio of the mixture to amorphous directing agent A1 is 1:0.6. Continue stirring for 1 hour and then transfer it to a hydrothermal reactor for crystallization reaction at 103℃ for 24 hours. Filter and wash the reaction product until the pH of the washing liquid is 7, and dry it at 80℃ for 20 hours to obtain a molecular sieve.
[0074] (3) Weigh 1.25g of zinc nitrate and dissolve it in 80mL of methanol and stir until completely dissolved. Weigh 1.05g of 2-methylimidazole and dissolve it in 80mL of methanol and stir until dissolved. Add 20g of the molecular sieve prepared in step (2) to the methanol solution of zinc nitrate until completely dissolved. Quickly pour the methanol solution of 2-methylimidazole into the above mixture and continue stirring for 3h. Then let the resulting solution stand at room temperature for 24h for aging. Then discard the supernatant. Wash the obtained precipitate with methanol by centrifugation and dry it in a vacuum oven at 50℃ for 12h. The obtained product is calcined in an argon atmosphere at 800℃ for 3h. Add 50mL of 0.5M hydrochloric acid solution to the carbonized product and stir continuously for 5h. After washing with deionized water by centrifugation, dry it in a vacuum oven at 50℃ for 12h to obtain ZIF-based derived porous carbon-molecular sieve composite material B1.
[0075] Table 1
[0076] Example 2 Preparation of amorphous directing agents: An aluminum source solution was prepared by mixing 10g of aluminum sulfate, 9.6g of sodium hydroxide, and 20g of deionized water. Then, a silicon source solution was prepared by dissolving 45g of silica sol in 20g of deionized water and stirring for 1 hour. The aluminum and silicon source solutions were mixed and reacted at 70°C for 6 hours to obtain amorphous directing agent A2. The molar ratio of Na2O / Al2O3 / SiO2 / H2O in the obtained amorphous directing agent A2 was 8:1:15:280.
[0077] Preparation of ZIF-derived porous carbon-molecular sieve composites: (1) Grind and mix 50g of fly ash and 80g of sodium carbonate, then place the resulting mixture in a muffle furnace and calcine at 620℃ for 2.5h. After cooling, fly ash clinker is obtained. The fly ash clinker and a 20% by weight hydrochloric acid solution are mixed at a mass ratio of 1:20 and filtered. The filtrate is collected to obtain aluminum-rich liquid, and the residue after filtration is separated.
[0078] (2) Take 20g of the residue filtered in step (1), 100g of sodium hydroxide and 200g of deionized water, stir and mix evenly, and filter the filtrate to obtain the silicon-rich liquid. Mix the aluminum-rich liquid and the silicon-rich liquid, and adjust the dosage ratio so that the SiO2 / Al2O3 ratio in the resulting mixture is 5. Then add a sodium nitrate solution with a concentration of 10% by weight, and adjust the dosage so that the Na2O / SiO2 molar ratio in the resulting mixture is 2.5. Add amorphous directing agent A2, and the mass ratio of the mixture to amorphous directing agent A2 is 1:0.6. Continue stirring for 1 hour and then transfer it to a hydrothermal reactor for crystallization reaction at 100°C for 30 hours. Filter and wash the reaction product until the pH of the washing liquid is 7, and dry it at 80°C for 20 hours to obtain a molecular sieve.
[0079] (3) Weigh 1.43g of zinc chloride and dissolve it in 80mL of methanol and stir until completely dissolved. Weigh 1.18g of terephthalic acid and dissolve it in 80mL of methanol and stir until dissolved. Add 20g of the molecular sieve prepared in step (2) to the methanol solution of zinc nitrate until completely dissolved. Quickly pour the methanol solution of 2-methylimidazole into the above mixture and continue stirring for 3h. Then let the resulting solution stand at room temperature for 30h for aging. Then discard the supernatant. Wash the obtained precipitate with methanol by centrifugation and dry it in a vacuum oven at 50℃ for 12h. The obtained product is calcined in an argon atmosphere at 900℃ for 2.5h. Add 50mL of 0.5M hydrochloric acid solution to the carbonized product and stir continuously for 5h. After washing with deionized water by centrifugation, dry it in a vacuum oven at 50℃ for 12h to obtain ZIF-based derived porous carbon-molecular sieve composite material B2.
[0080] Example 3 Preparation of amorphous directing agents: An aluminum source solution was prepared by mixing 10g of sodium aluminate, 4.8g of sodium hydroxide, and 10g of deionized water. Then, a silicon source solution was prepared by dissolving 90g of sodium silicate in 160g of deionized water and stirring for 1 hour. The aluminum and silicon source solutions were mixed and reacted at 60°C for 6 hours to obtain amorphous directing agent A3. The molar ratio of Na2O / Al2O3 / SiO2 / H2O in the obtained amorphous directing agent A3 was 7.2:1:5.2:200.
[0081] Preparation of ZIF-derived porous carbon-molecular sieve composites: (1) Grind and mix 50g of fly ash with 90g of sodium hydroxide, then place the resulting mixture in a muffle furnace and calcine at 750℃ for 1h. After cooling, fly ash clinker is obtained. The fly ash clinker and a 20% by weight sulfuric acid solution are mixed at a mass ratio of 1:20 and filtered. The filtrate is collected to obtain aluminum-rich liquid, and the residue after filtration is separated.
[0082] (2) Take 20g of the residue filtered in step (1), 130g of sodium hydroxide and 200g of deionized water, stir and mix evenly, and filter the filtrate to obtain the silicon-rich liquid. Mix the aluminum-rich liquid and the silicon-rich liquid, and adjust the dosage ratio so that the SiO2 / Al2O3 ratio in the resulting mixture is 6. Then add a sodium aluminate solution with a concentration of 10% by weight, and adjust the dosage so that the Na2O / SiO2 molar ratio in the resulting mixture is 2.2. Add amorphous directing agent A3, and the mass ratio of the mixture to amorphous directing agent A3 is 1:1. Continue stirring for 1 hour and then transfer it to a hydrothermal reactor for crystallization reaction at 85°C for 24 hours. Filter and wash the reaction product until the pH of the washing liquid is 7, and dry it at 80°C for 20 hours to obtain a molecular sieve.
[0083] (3) Weigh 1.56g of copper nitrate and dissolve it in 80mL of methanol and stir until completely dissolved. Weigh 1.22g of 2-methylimidazole and dissolve it in 80mL of methanol and stir until dissolved. Add 20g of the molecular sieve prepared in step (2) to the methanol solution of zinc nitrate until completely dissolved. Quickly pour the methanol solution of 2-methylimidazole into the above mixture and continue stirring for 3h. Then let the resulting solution stand at room temperature for 48h and then discard the supernatant. Wash the obtained precipitate with methanol by centrifugation and dry it in a vacuum oven at 50℃ for 12h. The obtained product is calcined in an argon atmosphere at 1000℃ for 2h. Add 50mL of 0.5M sulfuric acid solution to the carbonized product and stir continuously for 5h. After washing with deionized water by centrifugation, dry it in a vacuum oven at 50℃ for 12h to obtain ZIF-based derived porous carbon-molecular sieve composite material B3.
[0084] Example 4 ZIF-based derived porous carbon-molecular sieve composite material was prepared according to the method of Example 1, except that in step (3), 1.25g of zinc nitrate was replaced with a mixture of 625mg of zinc nitrate and 625mg of cobalt chloride to obtain ZIF-based derived porous carbon-molecular sieve composite material B4.
[0085] Example 5 ZIF-based derived porous carbon-molecular sieve composites were prepared according to the method of Example 1, except that in step (3), zinc nitrate was replaced with cobalt chloride to obtain ZIF-based derived porous carbon-molecular sieve composite material B5.
[0086] Example 6 ZIF-based derived porous carbon-molecular sieve composite material was prepared according to the method of Example 1, except that in step (3), the concentration of hydrochloric acid solution was adjusted from 0.5M to 2M to obtain ZIF-based derived porous carbon-molecular sieve composite material B6.
[0087] Example 7 ZIF-based derived porous carbon-molecular sieve composites were prepared according to the method in Example 1. The difference was that the amount of silicon source used was changed during the preparation of the amorphous directing agent, so that the molar ratio of Na2O / Al2O3 / SiO2 / H2O in the amorphous directing agent was 9.5:1:30:300, thus obtaining ZIF-based derived porous carbon-molecular sieve composite material B7.
[0088] Example 8 ZIF-based derived porous carbon-molecular sieve composite material was prepared according to the method of Example 1. The difference was that in the preparation process of the amorphous directing agent, the amount of silicon source used was changed so that the molar ratio of Na2O / Al2O3 / SiO2 / H2O in the amorphous directing agent was 9.5:1:30:300. In step (2), during the mixing of aluminum-rich liquid and silicon-rich liquid, the ratio of SiO2 / Al2O3 in the resulting mixture was adjusted so that the mass ratio of the mixture and the amorphous directing agent was 8. The mass ratio of the mixture and the amorphous directing agent was adjusted to 1:1.5 to obtain ZIF-based derived porous carbon-molecular sieve composite material B8.
[0089] Comparative Example 1 ZIF-based derived porous carbon-molecular sieve composite materials were prepared according to the method of Example 1, except that in step (3), hydrochloric acid solution was not added to the carbonized product for acid washing, and composite material D1 was obtained.
[0090] Comparative Example 2 The molecular sieve prepared in Example 1 was used as the comparative test sample D2.
[0091] Comparative Example 3 ZIF-based derived porous carbon-molecular sieve composite materials were prepared according to the method of Example 1, except that no calcination was performed in step (3) to obtain the comparative test sample D3.
[0092] The performance parameters of the materials prepared in the above embodiments and comparative examples are shown in Table 2 below.
[0093] Table 2
[0094] As can be seen from the results in Table 2, the ZIF-based derived porous carbon-molecular sieve composite material prepared according to the method described in this invention has a strong adsorption capacity for oxygen-containing compounds.
[0095] The preferred embodiments of the present invention have been described in detail above; however, the present invention is not limited thereto. Within the scope of the inventive concept, various simple modifications can be made to the technical solutions of the present invention, including combinations of various technical features in any other suitable manner. These simple modifications and combinations should also be considered as the content disclosed in the present invention and are all within the protection scope of the present invention.
Claims
1. A method for preparing a ZIF-based derived porous carbon-molecular sieve composite material, characterized in that, The method includes the following steps: (1) The fly ash and the first alkaline compound are mixed once, and the resulting mixture is calcined to obtain fly ash clinker. The fly ash clinker and the acid solution are mixed a second time and a solid-liquid separation is performed once to separate the first solid product and the first liquid product. (2) The first solid product, the second alkaline compound and water are mixed twice and then separated into solid and liquid phases twice. The separated second liquid product and the first liquid product are mixed three times. The resulting mixture, the sodium-containing salt solution and the amorphous directing agent are then subjected to a crystallization reaction to obtain a molecular sieve. (3) The molecular sieve, transition metal salt solution and organic ligand solution are mixed, and the resulting mixture is aged. The aged product is then separated into solid and liquid phases, and the separated solid product is calcined, acid washed and dried under an inert atmosphere.
2. The method according to claim 1, characterized in that, In step (1), the mass ratio of the fly ash to the first alkaline compound is 1:0.5-3; Preferably, the first alkaline compound is sodium hydroxide and / or sodium carbonate.
3. The method according to claim 1 or 2, characterized in that, In step (1), the calcination conditions include a temperature of 450-900℃ and a time of 0.5-4h.
4. The method according to any one of claims 1-3, characterized in that, In step (1), the mass ratio of the fly ash clinker to the acid solution is 1:1-60; Preferably, the acid solution is at least one selected from hydrochloric acid solution, sulfuric acid solution, nitric acid solution, and acetic acid solution; Preferably, the concentration of the acid solution is 10-50% by weight.
5. The method according to claim 1, characterized in that, In step (2), the mass ratio of the first solid product, the second alkaline compound, and the water is 1:(0.5-70):(0.5-500); Preferably, the second alkaline compound is at least one selected from sodium hydroxide, sodium carbonate, potassium hydroxide, and sodium bicarbonate.
6. The method according to claim 1 or 5, characterized in that, In step (2), the amounts of the second liquid phase product and the first liquid phase product are such that the molar ratio of SiO2 / Al2O3 in the resulting mixture is 1-8.
7. The method according to claim 1, 5, or 6, characterized in that, In step (2), the amounts of the obtained mixture and the sodium-containing salt solution are such that the Na2O / SiO2 molar ratio in the obtained mixture and the sodium-containing salt solution is 2-3; Preferably, the sodium-containing salt solution is at least one of sodium chloride solution, sodium nitrate solution, sodium bromide solution, and sodium aluminate solution; Preferably, the concentration of the sodium-containing salt solution is 5-15% by weight.
8. The method according to any one of claims 1 and 5-7, characterized in that, In step (2), the mass ratio of the obtained mixture to the amorphous directing agent is 1:0.01-1.
5.
9. The method according to any one of claims 1 and 5-8, characterized in that, In step (2), the conditions for the crystallization reaction include: a temperature of 60-108°C and a time of 1-48h.
10. The method according to any one of claims 1 and 5-9, characterized in that, The method further includes preparing the amorphous directing agent by reacting a silicon source, an aluminum source, an alkaline compound, and water at 40-100°C for 0.5-8 hours. Preferably, the silicon source is at least one selected from sodium silicate, silica sol, silicic acid, and water glass; Preferably, the aluminum source is at least one selected from aluminum sulfate, boehmite, aluminum sol, and sodium aluminate; Preferably, the alkaline compound is at least one selected from sodium hydroxide, potassium hydroxide, sodium bicarbonate, and sodium carbonate; Preferably, the amounts of the silicon source, the aluminum source, the alkaline compound, and the water are such that the molar ratio of Na2O / Al2O3 / SiO2 / H2O in the product is (1-10):1:(1-30):(1-500).
11. The method according to claim 1, characterized in that, In step (3), the mass ratio of the molecular sieve, the transition metal salt solution, and the organic ligand solution is 1:(1-5):(1-5); Preferably, the transition metal salt solution is at least one selected from zinc nitrate solution, zinc chloride solution, cobalt nitrate solution, cobalt chloride solution, ferric nitrate solution, ferric chloride solution, copper nitrate solution, copper chloride solution, and nickel nitrate solution; Preferably, the organic ligand solution is at least one selected from 2-methylimidazole, imidazole-2-carboxaldehyde, benzimidazole, and terephthalic acid.
12. The method according to claim 1 or 11, characterized in that, In step (3), the solvent used for the transition metal salt solution is at least one of methanol, ethanol, isopropanol, water, and n-butanol; Preferably, the concentration of the transition metal salt solution is 0.5-5% by weight.
13. The method according to claim 1 or 11, characterized in that, In step (3), the solvent used for the organic ligand solution is at least one of methanol, ethanol, isopropanol, water, and n-butanol; Preferably, the concentration of the organic ligand solution is 0.5-5% by weight.
14. The method according to any one of claims 1 and 11-13, characterized in that, In step (3), the aging conditions include: a temperature of 10-40°C and a time of 8-48 hours; and / or, In step (3), the calcination conditions include a temperature of 550-1000℃ and a time of 1-4h.
15. The method according to any one of claims 1 and 11-14, characterized in that, In step (3), the acid solution used in the pickling process is at least one of hydrochloric acid solution, nitric acid solution, acetic acid solution and sulfuric acid solution; Preferably, the concentration of the acid solution used in the pickling process is 0.5-2M.
16. A ZIF-based derived porous carbon-molecular sieve composite material prepared by the method according to any one of claims 1-15.
17. The application of the ZIF-based derived porous carbon-molecular sieve composite material according to claim 16 in the adsorption process of oxygen-containing compounds; Preferably, the oxygen-containing compound is a C5-C9 organic alcohol and / or a C5-C7 organic acid.
Citation Information
Patent Citations
An adsorbent for removing oxygen-containing compounds from low molecular weight hydrocarbons
CN115722189B
Adsorbent for adsorbing oxygenated compounds and method for adsorbing oxygenated compounds
CN116023982A